1993
DOI: 10.1152/jappl.1993.74.5.2127
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of tissue lipid to long xenon residence times in muscle

Abstract: Experiments demonstrate that the mean residence time of an inert gas in tissue is longer than that predicted by a single-compartment model of gas exchange. Also the relative dispersion (RD, the standard deviation of residence times divided by the mean) is 1 according to this model, but RDs in real tissues are closer to 2, suggesting that a multiple-compartment model might be more accurate. The residence time of a gas is proportional to its solubility in the tissue. Although the noble gases in particular are 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Firstly, we take the simulated data from 1 Au =− as the observations on MET ob U by difference scheme provided by Eq. (24). The data set has 2J points on escaping interval ( 1,1)…”
Section: Numerical Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, we take the simulated data from 1 Au =− as the observations on MET ob U by difference scheme provided by Eq. (24). The data set has 2J points on escaping interval ( 1,1)…”
Section: Numerical Experimentsmentioning
confidence: 99%
“…Lévy motion is a non-Gaussian process with heavy-tailed distribution and has been widely used in modeling various systems with heavy-tailed fluctuations [16][17][18] . Mean exit time, also called as mean residence time or mean first passage time, is a significant deterministic quantity and has been observed or measured in many systems such as fluid, industrial, chemical and physiological systems [19][20][21][22][23][24][25][26] . For instance, the mean residence time of a fluid particle can be measured by "pulse experiment 22 ", which consists of introducing a pulse of tracer in the inlet to the domain, while measuring continuously the tracer concentration at a given point.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mean residence time has been observed or measured in chemical, industrial and physiological systems [13,24]. For example, the mean residence time for Xe in intact and surgically isolated muscles can be measured [25]. It is found that the mean residence time of Xe is longer than that predicted by a single-compartment model of gas exchange, and this leads to the understanding that a multiple-compartment model might be more accurate according to larger relative dispersion (the standard deviation of residence time divided by the mean).…”
Section: Introductionmentioning
confidence: 99%